Forensic and reliability analyses of fixed dental prostheses. Issue 9 (1st February 2021) - Mecholsky, John J.; Hsu, Shu‐Min; Jadaan, Osama; Griggs, Jason; Neal, Daniel; Clark, Arthur E.; Xia, Xinyi; Esquivel‐Upshaw, Josephine F.
Abstract: This article describes the protocol for determining the cause of failure for retrieved failed implant supported fixed dental prostheses (FDPs) in a clinical study of three‐unit bridges. The results of loading of flexure bars of different veneer compositions at different stress rates were presented for two veneer materials (leucite reinforced and fluorapatite glass–ceramic veneers) and a Y‐TZP core zirconia ceramic used in the clinical study. From these results, the strengths of the fast loading conditions were used to determine the fracture toughness of these materials. Fractal dimension measurements of the flexure bars and selected FDPs of the same materials demonstrated that the values were the same for both the bars and the FDPs. This allowed the use of fracture toughness values from the flexure bars to determine the strengths of the FDPs. The failure analysis of clinically obtained FDP replicates to determine the size of the fracture initiating cracks was then performed. Using the information from the flexure bars and the size of the fracture initiating cracks for the failed FDPs, the strengths of the FDPs were determined. The clinical failures were determined to be most likely the result of repeated crack growth due to initial overload and continuous use after initial cracking.